2022
DOI: 10.1038/s41598-022-10774-z
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-EDTA-Cellulose network as a green, recyclable and multifunctional biopolymeric organocatalyst for the one-pot synthesis of 2-amino-4H-pyran derivatives

Abstract: In this research, cellulose grafted to chitosan by EDTA (Cs-EDTA-Cell) bio-based material is reported and characterized by a series of various methods and techniques such as FTIR, DRS-UV–Vis, TGA, FESEM, XRD and EDX analysis. In fact, the Cs-EDTA-Cell network is more thermally stable than pristine cellulose or chitosan. There is a plenty of both acidic and basic sites on the surface of this bio-based and biodegradable network, as a multifunctional organocatalyst, to proceed three-component synthesis of 2-amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 81 publications
0
29
0
Order By: Relevance
“…[64] Rostami et al used cellulose crosslinked in chitosan by EDTA (Ethylenediaminetetra-acetic acid) to produce a multifunctional organocatalyst (Cs-EDTA-Cell) with high thermal stability containing acidic and basic sites for the synthesis of 2amino-4H-pyran and its derivatives, which are widely known as insecticide, anticancer, DNA binder and anti-HIV, anti-inflammatory, antimalarial, antiviral and antihyperglycemic agent. [65] The organocatalyst was prepared in one-pot synthesis by solubilizing cellulose in sodium hydroxide, followed by the addition of chitosan and EDTA. The authors observed that the organo-…”
Section: Asymmetric Catalysts and Organocatalystsmentioning
confidence: 99%
“…[64] Rostami et al used cellulose crosslinked in chitosan by EDTA (Ethylenediaminetetra-acetic acid) to produce a multifunctional organocatalyst (Cs-EDTA-Cell) with high thermal stability containing acidic and basic sites for the synthesis of 2amino-4H-pyran and its derivatives, which are widely known as insecticide, anticancer, DNA binder and anti-HIV, anti-inflammatory, antimalarial, antiviral and antihyperglycemic agent. [65] The organocatalyst was prepared in one-pot synthesis by solubilizing cellulose in sodium hydroxide, followed by the addition of chitosan and EDTA. The authors observed that the organo-…”
Section: Asymmetric Catalysts and Organocatalystsmentioning
confidence: 99%
“…1–14 Hence, the use of renewable biopolymers such as cellulose, chitin, sodium alginate, and especially chitosan for the design and preparation of efficient biodegradable and heterogeneous organocatalytic systems would be very desirable. 11,15–39 Among these scaffolds, chitosan (CS) is one of the most unique and widely used biopolymers, a natural and active cationic amino polysaccharide obtained from the alkaline N -deacetylation of chitin. 8,24,40–47 Indeed, chitosan has numerous applications in various fields such as preparation of new bio-based materials, 48–52 heterogeneous catalytic systems, 38,53–55 water purification, metal extraction, 56–59 electrolyte-based fuel cells, 60–62 sensors, 6,63 corrosion protection, 64 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, multi-component reactions (MCRs) are the most desirable powerful synthetic route in which three or more reactants come together in a single reaction vessel to form a wide range of acyclic or heterocyclic compounds by one-pot processes. 38–41 MCRs afford extended molecular complexity and diversity from simple starting materials with high atom economy, which have found applications in medicinal and natural products chemistry. 42,43 Indeed, the most significant feature of MCRs is generating almost no by-products or simple molecules such as H 2 O or EtOH.…”
Section: Introductionmentioning
confidence: 99%